PTU-147 Validation Of Updated Barrett's Oesophagus Guideline Recommendations: Complications And Outcomes Of An 'adequate' Case Volume And The Feasibility Of Same Day Discharge. (9th June 2014) - Taylor, E; Din, S; Campbell, J; Hopper, A
Abstract : Introduction: Recent advances in the management of high grade dysplasia and early cancer in Barrett's oesophagus (BO) have led to updated guidelines recommending endoscopic resection (ER) as a first line option in selected cases. The complexity and complications of ER have prompted guidelines recommending at least 15 procedures annually per endoscopist to minimise complications. The reported complications of oesophageal perforation (<0.9%) and delayed bleeding (2–22%) may prompt routine overnight observation following resection. Our aim was to report complications and outcomes in a unit performing just above the recommended annual numbers of ER for BO. Methods: All patients undergoing ER for BO over 3 years were identified. All resections were performed with a mutiband ligation technique. Number of resections performed, size of resected specimens and stage of dysplasia/cancer in specimens were recorded. Complications of delayed bleeding, perforation, or dysphagia requiring dilation were also recorded. Results: In 3 years, 108 endoscopic resections were performed in 46 procedures (median resections per procedure=2; range 1–6). 3 patients underwent 2 separate procedures. Resected specimens ranged in size from 3–17 mm (mean 10mm, SD 2.77). Final histological diagnosis per procedure was: no dysplasia=6, low grade dysplasia=3, high grade dysplasia = 8, invasive cancer- T1a=9 T1b =13, T2=4. 2 ER specimens were not retrieved, 1 showed granular cell carcinoma. Immediate complications included 1 perforation (2.3%. 95% CI:0–13%) with successful closure at endoscopy. 2 procedures were abandoned due to immediate bleeding (4.6% 95% CI 4.2 to 16.0%) which was successfully treated at the time. Delayed bleeding occurred in 2 patients, (4.6% 95% CI 4.2 to 16.0%) requiring emergency OGD at 8 h and 11 days post procedure. The second required endotherapy and readmission for 7 nights. 7 patients developed post-ER dysphagia (15.9% 95% CI 7.6 to 29.7) requiring oesophageal dilation (median procedures = 2, range 1–5). There was no significant difference in the number of resections in patients who had perforation (1 ER) or bleeding (median 1 range 1–3) p = 0.56. Patients who developed symptomatic strictures had a significantly higher number of resections (median 4 range 1–6) p < 0.0001. Conclusion: Complication rates of Barrett's ER procedures in a unit performing an adequate number are comparable to published outcomes from high volume centres. Delayed bleeding is rare, occurring up to 7 days post procedure and is not more common within the first 24 h. Therefore, if no immediate complications occur, same day discharge is appropriate. Disclosure of Interest: None Declared.